Performance of reconstruction and identification of τ leptons decaying to hadrons and vτ in pp collisions at √s=13 TeV - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich; Baydali S. A. Sergey Anatolievich (2018, 2018)
Title screen